Optimalisasi Usaha Backyard Hatchery Ikan Kerapu Hibrida di Bali - Kardi, Cening; Slamet, Bejo; Pratiwi , Ni Putu Eka (Syntax Corporation, 2025)
This study aims to: (1) determine the productivity and survival rate of the Beautiful hybrid grouper backyard hatchery business using: a combination of copepod feed; a combination of feed without Copepod (which is usually done by); and a combination of feed with Algamax enrichment; (2) analyze the cost, return, and profit of the backyard hatchery business from each combination of feed use; and (3) design optimal techniques for the Beautiful Hybrid Grouper Backyard Hatchery business. The research was conducted in a survey and collaboration with 23 grouper hatchery backyard businesses. Data tabulation, graph descriptions, as well as t-tests of two samples are freely used for analysis. The Cantik hybrid grouper hatchery backyard business using a combination of Copepod feed provides productivity of 45400 heads; survival rate of 7.57%; and profit of IDR 48,475,000. The grouper fish hatchery backyard business with a combination of feed without Copepod (which is usually done by farmers) provided productivity of 63190 heads; survival rate of 10.53%; and profit of IDR 64,682,600. The backyard hatchery business that uses Algamax feed enrichment provides productivity of 74000 heads; survival rate of 12.33%; and profit of IDR 72,794,350. For the optimization of the Beautiful hybrid grouper backyard hatchery business, a combination of inputs was used, namely: 600 thousand grouper eggs; 2.5 kg of Sanofax2 pellets; Otohime A1 3.0 kg; Otohime B1 8.0 kg; Ottoman B2 9.0 kg; Otohime S1 10 kg; ALGAMAX feed enrichment of 114 g for Artemia culture, and 174 g for Rotifer culture; Rotifer 174 bags; Artemia 38 cans; 420 bags of shrimp; Medicine (Albazu) 3 sachets; and Workforce 2 people.